HIV infection as a risk factor for COVID 19: A systematic review and meta-analysis - Silvia Juliana Vásquez-Lozano (Asociación Colombiana de Infectología, 2023)
There are many questions about the behavior of coronavirus disease 2019 (COVID-19) in people living with human Immunodeficiency virus (PLHIV). It is not clear whether they have a higher risk of complications or higher mortality than the general population. The risk of infection of Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), risk of severe symptoms by COVID-19, and risk of mortality by COVID-19 of PLHIV were compared with people without human im-munodeficiency virus (HIV). EMBASE, PubMed, Scopus, Cochrane Library, Web of Science, LILACS and SCIELO were searched from January 2020 to March 2021. 22 cohort / case-control studies were chosen. Software Review Manager 5.4 was used for the meta-analysis. An increased risk of mortality (2.07) due to COVID-19 was identified among people with human immudeficiency virus (HIV) compared to people without HIV. HIV infection is a risk factor for COVID-19; it should be given special to patients with high viral load, low count CD4 and who are not currently receiving antiviral therapy (ART).